A novel low-cost indigenous goggle design for oxygen delivery in oxygen supplemented accelerated corneal collagen cross-linking. Issue 2 (March 2023) - Sinha, Rajesh; Sabir, Mohammed; Asif, Mohamed Ibrahime; Kalra, Nidhi; Kumar, Kanil Ranjith; Sinha, Renu
Purpose: Our study aims to describe a novel low-cost indigenous design of goggles for delivery of oxygen during oxygen supplemented accelerated corneal collagen cross-linking (CXL) Methods: The goggles were prepared by modifying the safety goggles available in personal protective equipment (PPE) kit. The goggle has two side openings covered with plugs. One plug was removed to insert a tubing for oxygen delivery at a rate of 5 litres/minute. A 20-gauge intravenous cannula was introduced from superior aspect of the goggle for measuring oxygen saturation in periocular environment. Results: The procedure could be successfully performed without any intraoperative difficulty with an oxygen concentration between 80–90% throughout procedure. The time to achieve maximum concentration after switching on oxygen supply was between 30–60 s. None of our patients complained of any discomfort due to goggles. There was no mechanical interference of the goggles with the UV delivery system and a focused UV light could be delivered. The opening in goggles allowed for uninterrupted alignment and centration of UV light at the corneal level. The effective cost of the goggles, canula and tubing amounted to 400INR (5.50USD). There was no distortion, kinking or slippage of the tubing allowing for uninterrupted oxygen flow. These goggles could be sterilized multiple times using plasma sterilization. Conclusion: The current modified cost-effective goggle design could be an effective alternative to the currently available oxygen delivery goggles, especially in a low resource setting.